Author index - The Editors, - (Nordic Archaeological Abstracts - NAA, 1975)
For practical reasons the alphabet employed is abc ... u v w x y (ii) z å (aa) li (æ) o ( ø). Finnish names beginning with aa will, however, be alphabetized as beginning with a double a. German li, o and il will be treated as Nordic å o and y. I and j, v and w are separated. lcelandic O and 1;> are equivalent to d and th.